(3GdSjGSI GdbVGFjI ddeMceI GdOSJhQjI GdYdjG (B: s (3OQGSI ebGQfI (B/ s - (3LGHQ eMeO MLjs; (3LGHQ LGO fUGQ (B: s; (3jSQj GdYUGQ (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2011)
(3JfGhdJ GdOQGSI GdhSGFd GdJj jSJNOegG GdbGVi GdOSJhQi aj JMbjb SjGSJg GdbVGFjI (B: (3h GdJj Jbhe CMjGfG Ydi JVjjb fWGb GdQbGHI h gh eG LQi JfGhdg (B: (3HYV UhQ gPG GdJVjjb eKd GSJHYGO CYeGd GdSjGOI ef fWGb GdQbGHI(B: (3h JbjjO eaghe TQW GdeUdMI (B: (3h JbjjO GSJNOGe QNUI GdJUOj cCMO hSGFd JMQjc GdOYhi GdOSJhQjI (B: (3h HjGf bQjfI GdOSJhQjI deUdMI GdJTQjY (B: (3h JbjjO GdQbGHI Ydi OSJhQjI GdJTQjYGJ GdUGOQI EYeGdG dfXQjI GdVQhQI (B: (3h Ydi OSJhQjI GdJTQjYGJ GdUGOQI HGdeNGdaI ddTQjYI GdESdGejIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2011.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B464 - 478s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOSJhQjs; (3GdSjGSI GdbVGFjIs; (3GSJbdGd GdbVGAs; (3GdaUd Hjf GdSdWGJs; (3TQW GdeUdMIs; (3CYeGd GdSjGOIs; (3QNUI GdJUOjs; (3dhGFM GdVQhQIs; (3dhGFM GdJahjVs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs